2020
DOI: 10.1152/physrev.00002.2019
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Toxicity of Drugs: When Drugs Turn Physiology into Pathophysiology

Abstract: Drugs are prescribed to manage or prevent symptoms and diseases, but may sometimes cause unexpected toxicity to muscles. The symptomatology and clinical manifestations of the myotoxic reaction can vary significantly between drugs and between patients on the same drug. This poses a challenge on how to recognize and prevent the occurrence of drug-induced muscle toxicity. The key to appropriate management of myotoxicity is prompt recognition that symptoms of patients may be drug related and to be aware that inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 396 publications
0
27
0
Order By: Relevance
“…The prescribed use of statin drugs reduces the risk of developing atherosclerotic cardiovascular disease (6,7), cardiovascularrelated death, and death in general, by lowering LDL-C levels (8)(9)(10). However, the use of statins on a regular basis has been associated with multiple adverse effects, including liver damage, liver necrosis, kidney damage, myopathy, and rhabodomyolysis (6,11,12), asks for the development of alternative agents or bioactives with cholesterol-lowering characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The prescribed use of statin drugs reduces the risk of developing atherosclerotic cardiovascular disease (6,7), cardiovascularrelated death, and death in general, by lowering LDL-C levels (8)(9)(10). However, the use of statins on a regular basis has been associated with multiple adverse effects, including liver damage, liver necrosis, kidney damage, myopathy, and rhabodomyolysis (6,11,12), asks for the development of alternative agents or bioactives with cholesterol-lowering characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the skeletal muscle parameters from the histological analysis in our study of the naringin treatment were higher than both the HFD and the HFD + SIM groups. A previous study showed that the effect of statin on the morphology of muscle fibres, induced myopathy, which comprised muscle atrophy, necrosis, and inflammation [ 36 ]. Similarly, the histological aspects of the muscle fibres in the HFD + SIM group in our study were split and had irregular shapes and sizes when compared with the control and naringin treatment groups, which is consistent with the previous study [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, drug-induced myopathies primarily cause weakness in proximal muscles of the legs and arms. 222 Whether this is consistent for children with cancer is unknown. Yang and Choi 74 followed 30 children (mean age: 10.9 ± 3.8) newly diagnosed with cancer (hematologic malignancies n = 19, solid tumors n = 11) during their first year of cancer treatment.…”
Section: Drug Therapymentioning
confidence: 99%